Assessment of longshore sediment transport rate using the CERC formula along the Batu Pahat coast, Malaysia - Mat Zain, Nur Amirah; Mokhtar, Mardiha; Daud, Mohd Effendi; Hamid, Nor Baizura; Abdul Rahman, Mohammad Ashraf; Ab Razak, Mohd Shahrizal (International Information and Engineering Technology Association, 2025)
Sediment transport is a key driver of coastal geomorphology and shoreline stability. Longshore sediment transport (LST), primarily influenced by wave action and nearshore currents, plays a significant role in coastal evolution. This study assesses the longshore sediment transport rate (LSTR) along the Batu Pahat coastline in Malaysia, using empirical models, particularly the Coastal Engineering Research Center (CERC) formula. Three coastal areas, Pantai Parit Hailam (PH), Pantai Punggur (PG), and Pantai Perpat (PP), were selected due to active sediment redistribution and erosion. Sediment sampling was conducted in the field, whereas wave characteristics, including significant wave height, wind speed, and mean wave direction, were derived from the European Centre for Medium-Range Weather Forecasts (ECMWF) database. Calculated LSTR values ranged from 0.0033 to 0.0062 m3/s, reflecting spatial variations driven by oblique waves and hydrodynamic conditions. The highest LSTR (0.0062 m3/s at PH 1) was linked to higher wave energy and more oblique wave angles, while the lowest (0.0033 m3/s at PG 2) was attributed to sediment retention behind revetment structures. Variations in transport dynamics were also influenced by differences in coastal topography and sediment characteristics, consistent with previous studies on erosion and sediment redistribution. The findings underscore the need for targeted coastal management strategies, including groins, breakwaters, and beach nourishment, to mitigate sediment loss and enhance shoreline resilience.